USE OF DIFFERENT PROBIOTICS FOR PREVENTION OF VIBRIOSIS DISEASE ON TIGER SHRIMP LARVAE REARED IN FIBERGLASS TANKSUSE OF DIFFERENT PROBIOTICS FOR PREVENTION OF VIBRIOSIS DISEASE ON TIGER SHRIMP LARVAE REARED IN FIBERGLASS TANKS - Nurbaya Nurbaya; Muharijadi Atmomarsono (Indonesian Aquaculture Journal, 2018)
To counter disease problems caused by vibriosis in shrimp hatchery, this recent study used three different probiotics to be tested on tiger shrimp (Penaeus monodon) postlarvae. The study arranged four treatments as follows: A: a combination of three liquid-form probiotics Brevibacillus laterosporus BT951, Bacillus subtilis BM12, and B. licheniformis BM58; B: a combination of three powder-form probiotics Brevibacillus laterosporus BT951, Bacillus subtilis BM12, and B. licheniformis BM58; C: a commercial powder probiotic containing Bacillus subtilis; and D: control (without probiotic), each treatment with three replications. This study was set up in a completely randomized design experiment using twelve fiberglass tanks filled with 750 L sterile sea water and stocked with 30,000 nauplii in the Awarange shrimp hatchery of the Research Institute for Brackishwater Aquaculture and Fisheries Extension Installation in Barru. Variables observed in this study were the survival rate of the shrimp postlarvae at the end of the experiment, total vibrio count (TBV) and total plate count of common bacteria (TPC) in the culture water. The results showed that the survival rate of tiger shrimp applied either in liquid (A: 61.5±4.7%) or powder form (B: 48.6±6.8%), and control (without probiotic) (D: 51.2±4.4%) were not significantly different (P>0.05). However, survival rates in these three treatments differed (P<0.05) with that of the commercial probiotic (C: 21.7±9.9%). TBV/TPC ratio in the tank waters treated with the commercial probiotic (2.26-37.52%) was much higher than that of the liquid form probiotic (0.86-1.98%), powder form probiotic (1.25-8.37%), and control (1.93-2.84%). Ammonia-nitrogen in treatment C (1.462-2.989 mg/L) was relatively higher than that of in treatment A (1.595-2.435 mg/L), treatment B (1.644-2.115 mg/L), and treatment D (1.051-1.858 mg/L).